Epidermal growth factor receptor (EGFR)—MAPK—nuclear factor(NF)‐κB—IL8: A possible mechanism of particulate matter(PM) 2.5‐induced lung toxicity. Issue 5 (19th January 2017) - Jeong, Seung‐Chan; Cho, Yoon; Song, Mi‐Kyung; Lee, Eunil; Ryu, Jae‐Chun
Abstract: Airway inflammation plays a central role in the pathophysiology of diverse pulmonary diseases. In this study, we investigated whether exposure to particulate matter (PM) 2.5, a PM with an aerodynamic diameter of less than 2.5 µm, enhances inflammation‐related toxicity in the human respiratory system through activation of the epidermal growth factor receptor (EGFR) signaling pathway. Through cytokine antibody array analysis of two extracts of PM2.5 [water (W‐PM2.5 ) and organic (O‐PM2.5 ) soluble extracts] exposed to A549 (human alveolar epithelial cell), we identified eight cytokines changed their expression with W‐PM2.5 and three cytokines with O‐PM2.5 . Among them, epidermal growth factor (EGF) was commonly up‐regulated by W‐PM2.5 and O‐PM2.5 . Then, in both groups, we can identify the increase in EGF receptor protein levels. Likewise, increases in the phosphorylation of ERK1/2 MAP kinase and acetylation of nuclear factor(NF)‐κB were detected. We also detected an increase in IL‐8 that was related to inflammatory response. And using the erlotinib as an inhibitor of EGFR, we identified the erlotinib impaired the phosphorylation of EGFR, ERK1/2, acetylation of NF‐κB proteins and decreased IL‐8. Furthermore, at in vivo model, we were able to identify similar patterns. These results suggest that PM2.5 may contribute to an abnormality in the human respiratory system through EGFR, MAP kinase, NF‐κB, and IL‐8 induced toxicity signaling. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1628–1636, 2017.